2016
DOI: 10.1080/09537287.2016.1185188
|View full text |Cite
|
Sign up to set email alerts
|

A Lean Six Sigma framework for the reduction of ship loading commercial time in the iron ore pelletising industry

Abstract: Evidence suggests that specifically designed frameworks to implement Lean Six Sigma (LSS) projects to tackle particular problems are more effective than "generic" versions. This paper proposes an implementation framework to effectively deploy LSS to improve a key operation and performance indicator, i.e. ship loading commercial time, of one of the largest world producer of iron ore. This article therefore contributes with a refined framework to effectively implement LSS, and documents its successful applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 48 publications
2
49
0
1
Order By: Relevance
“…In recent times, the high volume of published work using the case study research method (e.g. Garza-Reyes et al, 2016a;Villarreal et al, 2016;Garza-Reyes et al 2016b;Bevilacqua et al, 2015; among many others) indicates its well acceptance in the scholarly literature. Despite this wide acceptance within the academic community as a valid research methodology, the case study approach may still be considered as a limited research method to conclusively validate the effectiveness of the proposed model.…”
Section: Cases Studymentioning
confidence: 99%
“…In recent times, the high volume of published work using the case study research method (e.g. Garza-Reyes et al, 2016a;Villarreal et al, 2016;Garza-Reyes et al 2016b;Bevilacqua et al, 2015; among many others) indicates its well acceptance in the scholarly literature. Despite this wide acceptance within the academic community as a valid research methodology, the case study approach may still be considered as a limited research method to conclusively validate the effectiveness of the proposed model.…”
Section: Cases Studymentioning
confidence: 99%
“…The mining and automotive sectors intersect, as the first typically comprises individual and stand-alone business units that seek business improvement methods to pursue a reduction of operating costs, increase productivity and efficiency (Klippel et al 2008a;Chlebus et al 2015), achieve process optimisation (Castillo et al 2015), meeting targets and plans (Dunstan et al 2006), improve internal communications (Castillo et al 2015), and customers satisfaction (Garza-Reyes et al 2016). Fig.…”
Section: Reporting and Using The Resultsmentioning
confidence: 99%
“…More importantly, a few academics in the studies under review paid close attention to critical-to-satisfaction factors of their clients. These factors reflect a need for the voice of the customer (Garza-Reyes et al 2016) to be captured as organisational inputs and interpreted for business improvement outputs by Lean practices. A study by Castillo et al (2015) clearly shows that parameters for the study were elaborated in accordance to the goal, identified by the mining organisation-client.…”
Section: Current Lean Approaches In the Mining Industrymentioning
confidence: 99%
“…Measure phase is the second phase which most of the tools are adopted to collect data, to understand current organization which basically to understand "What-Is" scenario data [22]. However, [23], [24] utilized this phase to explore and to investigate the base line of manufacturing process.…”
Section: B Lean Six Sigma (Lss)mentioning
confidence: 99%
“…There were many studies done to compare Lean and Agile approaches in terms of principles, methodologies, practices and tools to assist the researcher to evaluate and characterize similarities and differences at different perspective. Authors in [32], [23] performed a comparative study between Agile Methodologies towards Heavyweight software development by analyzing the differences between Waterfall and Agile in principles, project size, perspectives and strategies. Author in [34] presented the comparison study of seven agile methodologies to understand the characteristics, advantages and disadvantages.…”
Section: Comparative Studymentioning
confidence: 99%